Use of Surfactant in Photogalvanic Cell for Solar Energy Conversion and Storage: TX-100-Glycerol-Azure-C System - Gunsaria, R.K.; Hussain, J. (Asian Journal of Chemistry, 2010)
The photovoltaic cells involve direct excitation of an electron by a photon and thus producing electricity. The photovoltaic cells have high conversion efficiency but lack of storage capacity whereas the photogalvanic cells are based on some chemical reactions which give rise to high energy products on excitation by photon and these energy-rich products lose energy electrochemically. The efforts have been made to rich a desired amount of conversion efficiency and storage capacity by the addition of surfactants. The photogalvanic cells containing glycerol as reductant, Azure-C as photosensitizer and Triton X-100 as neutral surfactant have been investigated for solar energy and storage. The photopotential, photocurrent and power generated by this photogalvanic cell were 675.0 mV, 130.0 μA and 87.750 μW respectively. The conversion efficiency of the cell was determined as 0.4704% and fill factor was 0.4351. The current voltage characteristics of the cell have also been studied. The effect of different parameters of electrical output of the cell was investigated and a mechanism for the generation of the photocurrent in this photogalvanic cell has also been proposed.